Managerial Determinants of Public Service Performance in the Rancabali Subdistrict, Bandung Regency: The Mediating Role of Innovation - Pratama, Hangga Anugratyas; Ali, Mochammad Mukti (Dinasti Publisher, 2025)
This study investigates the direct and mediated effects of transformational leadership, human resource competence and budget efficiency on public service performance in the Rancabali Subdistrict Government, Bandung Regency. Innovation acts as a mediating mechanism connecting these managerial variables to service outcomes. Despite growing levels of citizen satisfaction, performance improvement remains limited, raising concerns about the effectiveness of managerial interventions. Applying an explanatory quantitative design, the study collected data from 30 structured questionnaires and conducted semi-structured interviews with six local government officials. Results from multiple linear regression and mediation analysis using PROCESS Macro v5.0 reveal that human resource competence is the most significant predictor of service performance (? = 0.634; p = 0.001), although it shows no influence on innovation (? = –0.087; p = 0.545). Budget efficiency does not directly affect performance (? = –0.077; p = 0.469) but significantly promotes innovation (? = 0.199; p = 0.032), which fully mediates its relationship with performance (95% CI: 0.019 to 0.332). Similarly, transformational leadership indirectly enhances performance through innovation (? = 0.458; p = 0.004). These findings emphasize innovation as a strategic pathway through which leadership and budgeting can be converted into measurable improvements in service delivery under constrained bureaucratic conditions.